Photocatalytic degradation of aflatoxin B1 based on prussian blue nanoflower - ZHANG Tianyu; XIE Xinhui; LU Yan; LU Dai; SHI Xingbo (Shipin yu jixie)
ObjectiveTo achieve efficient and environmentally friendly degradation of Aflatoxin B1 (AFB1).MethodsThis work employs a nucleic acid-mediated methodology to synthesize Prussian Blue Nanoflowers (PBNFs) characterized by highly efficient photo-Fenton catalytic activity, investigating their photodegradation efficacy and mechanisms against Aflatoxin B1 (AFB1).ResultsThe findings reveal that, under near-infrared light irradiation (NIR), 0.5 μg/mL of AFB1 can be completely eliminated within 4 h, which is attributed to the exceptional photo-Fenton performance of the PBNFs photocatalyst. Optimization experiments indicate that increasing the concentrations of hydrogen peroxide (H2O2) and PBNFs, along with enhancing light intensity, significantly facilitates the photocatalytic degradation of AFB1. Reactive oxygen species generated from H2O2 decomposition, triggered by NIR irradiation of PBNFs, effectively disrupt the terminal furan double bond and the benzene ring side chain of AFB1. Mass spectrometry analysis was conducted to elucidate the degradation products of AFB1, and cytotoxicity assays demonstrated a significant reduction in the toxicity of the AFB1 degradation products. The proposed method was applied to the degradation of AFB1 in three wine samples, achieving degradation rates of 66.6%, 90.8%, and 63.4%, respectively.ConclusionThis method provides an efficient and environmentally benign approach to the degradation of AFB1 in food samples.